Accounting Teachers’ Readiness for Virtual Classroom During the Covid-19 Pandemic, South Africa - Skhephe, Melikhaya (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2022)
Accounting education is crucial because it establishes the core knowledge required for education and growth in any country. During COVID-19, teachers in Accounting schools, like those in other educational institutions, were expected to adopt virtual classroom to continue their educational activities. This study aimed to demonstrate the virtual classroom readiness of Accounting school teachers in South Africa during the Covid-19 pandemic. The study employed qualitative research methods in this study, and the case study research design was used to explore the reality about virtual classroom readiness of Accounting school teachers and semi-structured interviews and thematic content analysis were employed to generate data. Results show that teachers are not prepared to implement virtual classroom during the Covid-19, according to the findings, and no one is assisting them. Another result indicated that virtual classroom facilities are lacking in schools. Education officials should offer ongoing virtual classroom courses for teachers, according to the study. In this study author concludes that, in order for instructors to be prepared for virtual classroom, educational administrators must oversee its implementation. In this study the author recommends that teachers must notify people in charge of education about what needs to be done in order to provide high-quality instruction.